Serotonin Syndrome Following Methylene Blue Administration for Vasoplegic Syndrome. Issue 4 (2nd March 2016) - Hencken, Laura; To, Long; Ly, Nancy; Morgan, Jeffrey A.
Abstract: Methylene blue (MB) has been used for additional blood pressure support in patients who develop severe, refractory vasoplegia; however, MB can induce serotonin syndrome, especially when used in conjunction with other serotonergic agents. We describe a case of serotonin syndrome in a patient who received MB for vasoplegic syndrome after left ventricular assist device implantation and discuss its presentation and management. doi: 10.1111/jocs.12705 (J Card Surg 2016;31:208–210)